A composite steel plate shear walls for offshore constructions - Albarody, T.M.B. (EDP Sciences, 2014)
A new-type of weldable composite steel plate shear wall, which consists of a steel plate sandwiched by either of two or one composite panels at each side or at one side, has been proposed. An analytical model for such shear wall - via shell model is derived and the vibrational modes are discussed. Truss reinforcement is used to increase the integration between the steel and composite layers and the cross sectional properties were graded by magnetic nanoparticles fillers. The thickness shear modes at the composite wall appear higher than those of thickness stretch modes, but they are varied in a very orderly manner with respect to the vibrational mode. Also, some of characteristics are examined. Â© 2014 Owned by the authors, published by EDP Sciences.